2017
DOI: 10.1088/1361-6463/aa7319
|View full text |Cite
|
Sign up to set email alerts
|

Uniform magnetization dynamics of a submicron ferromagnetic disk driven by the spin–orbit coupled spin torque

Abstract: A simple model of magnetization dynamics in a ferromagnet/doped semiconductor hybrid structure with Rashba spin-orbit interaction (SOI) driven by an applied pulse of the electric field is proposed. The electric current excited by the applied field is spin-polarized due to the SOI and therefore it induces the magnetization rotation in the ferromagnetic layer via s-d exchange coupling. Magnetization dynamics dependence on the electric pulse shape and magnitude is analyzed for realistic values of parameters. We s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…It seems to be naively believed that a timedependent current should provide more adjustability. By an appropriate linearization, Bondarenko and Sherman [51] decomposed the magnetization dynamics as a superposition of the in-plane precession and outof-plane nutation and confirmed that the pulse shape and magnitude of the alternating current can control the magnetization oscillation and switching. From an application viewpoint, a time-dependent current favors improving energy efficiency.…”
Section: Discussionmentioning
confidence: 94%
“…It seems to be naively believed that a timedependent current should provide more adjustability. By an appropriate linearization, Bondarenko and Sherman [51] decomposed the magnetization dynamics as a superposition of the in-plane precession and outof-plane nutation and confirmed that the pulse shape and magnitude of the alternating current can control the magnetization oscillation and switching. From an application viewpoint, a time-dependent current favors improving energy efficiency.…”
Section: Discussionmentioning
confidence: 94%
“…The dynamic properties of magnetic materials or devices are interesting research areas because of their vast frequency tuning range from several megahertz to gigahertz and even terahertz [1][2][3][4]. The total energy of a ferromagnetic unit is determined by the competition among the exchange field, demagnetization field, external field and anisotropic field etc.…”
Section: Introductionmentioning
confidence: 99%